Investigating the impact of steroid dependence on gastrointestinal surgical outcomes from UK Biobank - Uri Kartoun; Akira Koseki; Akihiro Kosugi; Kingsley Njoku; Tesfaye Yadete; Eileen Koski; Joao Bettencourt-Silva; Natasha Mulligan; Jianying Hu; Julia Liu; Thaddeus Stappenbeck; Vibha Anand (Scientific Reports)
Abstract Although corticosteroids are an important treatment for inflammatory bowel disease (IBD) patients, many subjects develop dependence, leading to serious long-term side effects. We applied causal inference analyses to investigate the length of steroid use on reoperations in IBD patients. We identified subjects in the UK Biobank general practice dataset with at least one major GI surgery and followed them for at least 5 years to evaluate subsequent operations. We defined steroid dependence as at least 12 weeks of use (vs. acute steroid use) prior to baseline surgery. Of the 363 subjects included in our analyses, 163 (45%) were prescribed steroids on or before baseline surgery, and of these (N = 125 of 163, 77%) were dependent. Additional analyses for time-dependent data on prescriptions found a link between prescription length and reoperation. Among UC subjects with acute use, the odds of reoperation were significantly lower (OR: 0.32, 95% CI: 0.0–0.73). Steroid dependence resulted in a delay of reoperation (median 1.2 vs. 2.3 years, P = 0.01). Our findings indicate that long-term steroid use tends to increase the need for reoperation, whereas short-term use may reduce it.